2022
DOI: 10.1523/jneurosci.2521-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Gentle Immunopurification of Brain Synaptic Vesicles

Abstract: Current methods to isolate synaptic vesicles (SVs), the organellar quanta of synaptic transmission, require highly specialized materials and up to 24 hours. These technical obstacles have thus far limited the study of SVs in models of synaptic function and pathophysiology. Here, we describe techniques for the rapid isolation of SVs by immunoprecipitation with widely available antibodies conjugated to magnetic beads. We report that the inexpensive rho1D4 monoclonal antibody binds SVs and show that elution with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 54 publications
(124 reference statements)
3
36
0
Order By: Relevance
“…Alongside synaptosomes, a highly pure population of SVs was isolated by immunoprecipitation (IP) with magnetic beads conjugated in-house to a monoclonal antibody against SV2 (Buckley and Kelly, 1985), according to recently described procedures ( Fig. 1A ) (Bradberry et al, 2022). These preparations were subjected to proteomic analysis by trypsin digestion and nano-flow liquid chromatography-tandem mass spectrometry (nLC-MS/MS) using an Orbitrap Eclipse mass spectrometer (Bradberry et al, 2022) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside synaptosomes, a highly pure population of SVs was isolated by immunoprecipitation (IP) with magnetic beads conjugated in-house to a monoclonal antibody against SV2 (Buckley and Kelly, 1985), according to recently described procedures ( Fig. 1A ) (Bradberry et al, 2022). These preparations were subjected to proteomic analysis by trypsin digestion and nano-flow liquid chromatography-tandem mass spectrometry (nLC-MS/MS) using an Orbitrap Eclipse mass spectrometer (Bradberry et al, 2022) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1E ). This represents the largest number of proteins detected in a highly pure SV preparation to date (Bradberry et al, 2022; Taoufiq et al, 2020). Label-free quantitation (LFQ) intensity scores of synaptosome and SV proteins were positively correlated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, consistent with our present findings, even in worms ATG9A did not appear to precisely colocalize with SVs: 1) its localization clearly diverged from the localization of SVs after perturbation of endocytosis 22,24 and 2) the localization of SV proteins and of ATG9A was differentially affected by genetic perturbation of the active/periactive zone protein Clarinet 24 . Moreover, while mass spectrometry analysis of purified SV fraction from rat brain detected ATG9A in such vesicles [25][26][27] , the amount of ATG9A detected was extremely low 26 . It was estimated that 4 copies of ATG9A were present in 100 vesicles 26 .…”
Section: Discussionmentioning
confidence: 97%
“…ATG9A is present in axon terminals where, together with other autophagy factors, it plays an important role in synapse development and homeostasis [22][23][24] . Proteomic studies have detected ATG9A (at low copy number) in purified SV fractions [25][26][27] . Moreover, recent imaging studies have shown that synaptically-localized ATG9A undergoes exo-endocytosis in response to activity in parallel with bona fide SV proteins 22,24 .…”
mentioning
confidence: 99%
“…Syt1 binds Ca 2+ with lower affinity (4), and responds to changes in [Ca 2+ ] with faster kinetics than syt7 (5). Syt1 is localized to SVs (2,(6)(7)(8), where it clamps spontaneous release (9,10) under resting conditions. Then, upon depolarization and Ca 2+ entry (11,12), syt1 functions to trigger and synchronize evoked release (9,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%